Daily home spirometry to detect early steroid treatment effects in newly treated pulmonary sarcoidosis. Issue 1 (18th January 2018) - Broos, Caroline E.; Wapenaar, Monique; Looman, Caspar W.N.; in 't Veen, Johannes C.C.M.; van den Toorn, Leon M.; Overbeek, Maria J.; Grootenboers, Marco J.J.H.; Heller, Roxane; Mostard, Rémy L.; Poell, Linda H.C.; Hoogsteden, Henk C.; Kool, Mirjam; et al.
Prednisone is the mainstay of sarcoidosis treatment. However, prednisone treatment optimisation is warranted, since prolonged high-dose prednisone therapy is associated with burdensome and harmful side-effects [1, 2]. Early prednisone dose tapering has the potential to reduce side-effects. Gaining insight in the early treatment response can help to determine when tapering could be initiated. To date, there are no prospective studies that look at early treatment response to prednisone in sarcoidosis by monitoring clinical symptoms and daily patient-administered lung function. Therefore, we initiated a multicentre, prospective and observational study with daily home spirometry to detect early steroid treatment effects in newly treated pulmonary sarcoidosis (Dutch National Trial Register NTR4328;www.trialregister.nl/trialreg ). The major treatment effect of prednisone on FVC is reached within 2 to 3 weeks in newly treated sarcoidosis patients http://ow.ly/3A3E30h5ZuT